OBJEK, MODEL, DAN LINGKUNGAN SEBAGAI MEDIA PEMBELAJARAN DALAM PROSES PEMBELAJARAN DI KELAS - Rusiadi (CV. Adiba Aisha Amira, 2026)
Object, model, and environmental learning media are types of concrete media that play a strategic role in the learning process. Real objects provide authentic direct experience for students through genuine interaction with actual items. Models serve as solutions when real objects cannot be brought to the classroom due to size, distance, or safety constraints. Meanwhile, the environment as a learning medium utilizes the real-life context surrounding students as a rich and meaningful learning resource. This study aims to comprehensively analyze the concepts, characteristics, advantages, limitations, and implementation. The method employed is qualitative library research. The findings indicate that the appropriate and planned use of objects, models, and the environment can enhance the quality of learning experiences, strengthen conceptual understanding, and encourage active student engagement in the learning process.